Pakistan's Security : The Challenge and The Response - Khan, Zulfiqar Ali (Air Chief Marshal Retd. ) (Lahore Progressive Publishers, 1988)
A thorough and balanced study of Pakistan's geopolitics in the period after the soveit military intervention in Afghanistan.
Keywords: National Security -- World Politics